2018
DOI: 10.1093/aob/mcy113
|View full text |Cite
|
Sign up to set email alerts
|

Origin and parental genome characterization of the allotetraploidStylosanthes scabraVogel (Papilionoideae, Leguminosae), an important legume pasture crop

Abstract: Our approach combined whole-plastome and rDNA assembly with additional cytogenetic analysis to shed light successfully on the allotetraploid origin of S. scabra. We propose a Middle Pleistocene origin for S. scabra involving species with maternal A and paternal B genomes. Our data also suggest that variation found in rDNA units in S. scabra and its progenitors reveals differences that can be explained by homogenization, deletion and amplification processes that have occurred since its origin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 89 publications
3
30
0
Order By: Relevance
“…Although most of the species of the genus Stylosanthes are diploids, few polyploid species, such as S. hamata and S. scabra with 2n= 40, and S. erecta with 2n=60 were reported (Cameron, 1967;Karia, 2008;Polido et al, 2015). The diploid chromosome number (2n = 2x = 20) here observed is in agreement with previous report for the genus Stylosanthes (Vieira et al, 1993;Lira, 2015;Marques et al, 2018). Mor- 6 Franco et al phometric analysis of the Stylosanthes karyotypes revealed that the chromosomal profile was similar for all diploid species previously investigated (Vieira et al, 1993), corroborating our findings.…”
Section: Karyotype Stability In Stylosanthessupporting
confidence: 93%
See 3 more Smart Citations
“…Although most of the species of the genus Stylosanthes are diploids, few polyploid species, such as S. hamata and S. scabra with 2n= 40, and S. erecta with 2n=60 were reported (Cameron, 1967;Karia, 2008;Polido et al, 2015). The diploid chromosome number (2n = 2x = 20) here observed is in agreement with previous report for the genus Stylosanthes (Vieira et al, 1993;Lira, 2015;Marques et al, 2018). Mor- 6 Franco et al phometric analysis of the Stylosanthes karyotypes revealed that the chromosomal profile was similar for all diploid species previously investigated (Vieira et al, 1993), corroborating our findings.…”
Section: Karyotype Stability In Stylosanthessupporting
confidence: 93%
“…The number of 5S and 35S rDNA sites was assumed as continuous data. Chromosome data of species were taken from the literature (Marques et al, 2018) or from this work, and they were treated as an unordered, multistate character.…”
Section: Phylogenetic Analysis and Character Reconstructionmentioning
confidence: 99%
See 2 more Smart Citations
“…Stylo (Stylosanthes spp.) is an important forage legume that is widely used in agricultural systems in tropical and subtropical areas, where acid soils are widely distributed [45]. P deficiency, along with Al and manganese (Mn) toxicity, are considered as the major limiting factors for crop growth and production in acid soils [46].…”
Section: Introductionmentioning
confidence: 99%